Combination of zinc and probiotic for acute diarrhoea in adult - Riadi, Putu Risma Yuvita; Dewi , Anak Agung Istri Sri Kumala (International Journal of Advances in Medicine, 2024)
In Indonesia, diarrhea affected 9% of the population and was the fourth most common cause of death across all age groups (13.2%). Case 1: A 33-year-old female presented to the emergency room with a history of diarrhea without bloody or oily stools, nausea and vomiting. The patient was assessed with noninfective gastroenteritis, suspected to be caused by viruses. She was given rehydration therapy, symptomatic therapy, with combination of zinc and probiotic. Case 2: A 25-year-old female presented to the emergency room with a history of diarrhea without bloody or oily stools and mild epigastric pain. The patient was assessed with noninfective gastroenteritis, suspected to be caused by viruses. She was given rehydration therapy, symptomatic therapy, with combination of zinc and probiotic. The primary foundation treatment for acute diarrhea includes prescribing zinc and probiotic supplements to aid in recovery. Probiotics may have an impact on a variety of innate and acquired immunity-related cells, while zinc is an essential element of all highly proliferating cells in the human body. It plays a critical role in modulating resistance to infectious agents and reduces the duration, severity, and risk of diarrheal disease. Our case highlights that, combination of zinc and probiotic give a significant effect not only in children, but also in adult. Zinc and probiotic can help fasten the recovery phase of diarrhea and decrease the mean duration of acute diarrhea.